The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1037/0012-1649.35.6.1379
|View full text |Cite
|
Sign up to set email alerts
|

Maternal care and attachment security in ordinary and emergency contexts.

Abstract: One of the foundations of attachment theory is the notion that early care plays a key role in determining the quality of child-caregiver attachment relationships. Studies have consistently shown relations between maternal sensitivity and infant security. Further research is required to resolve issues arising from modest correlations, focus on research in stressful as opposed to ordinary contexts, and questions about the generality of results across cultures and social contexts and about the context specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
2
19

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 38 publications
5
68
2
19
Order By: Relevance
“…Even for the same caregiver behaviours will vary according to situations and contexts, but the results for the child will be the same. From the child's point of view, what is important is that he/she learns that the parent is responsive, co-operative, and available as needed (Posada et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Even for the same caregiver behaviours will vary according to situations and contexts, but the results for the child will be the same. From the child's point of view, what is important is that he/she learns that the parent is responsive, co-operative, and available as needed (Posada et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Also, their results showed that the dyads with more positive resources in their families showed, among the three groups, the highest correlations between maternal sensitivity and attachment security. However, data from a study realized in Colombia by Posada and collaborators [38]comparing two samples, one middle class and one in extreme poverty, showed a significant and robust association between these two variables. Nevertheless, in this study the mean scores for maternal sensitivity and attachment security were significantly lower than those from the socioeconomically advantaged.…”
Section: Parenting and Vulnerabilitymentioning
confidence: 93%
“…Studies from Chile, Columbia and South Africa show maternal sensitivity was associated with more secure infant attachment, cognitive ability and reduced levels of behaviour problems in preschool children [20][21][22] . Maternal sensitivity is the most crucial for child development.…”
Section: *Address Given On Induction As President Slcp November 2009mentioning
confidence: 99%